Compact dual‐band quasi‐Yagi antenna with pattern diversification for WI‐FI 6E applications. Issue 10 (16th June 2022) - Hong, Dingmou; Yu, Yaqing; Yi, Da; Ye, Mao; Tang, Ming‐Chun
Abstract: A dual‐band quasi‐Yagi antenna with diverse radiation patterns at different frequency bands is presented for the Wi‐Fi 6E applications. It has multiple working bands that cover the two existing bands of traditional Wi‐Fi 6, that is, from 2.4–2.4835 to 5.17−5.835 GHz, as well as the upcoming extended Wi‐Fi 6E band that covers the 5.925−7.125 GHz band. The proposed antenna consists of a microstrip (MS) line, a coplanar strip‐line (CPS), a bow‐tie driven dipole element, a slotted ground plane and a parasitic director element. By jointly employing these structures, multiple resonances can be generated, where the resonance with largest current path results in low‐frequency working band, while the others are merged to form a relatively wide high‐frequency band. In the low‐frequency band, the antenna has an omnidirectional radiation pattern with wide beam‐coverage, while in the high‐frequency band, the antenna can achieve directional radiation pattern with high gain value. An antenna prototype is then fabricated and measured for validation. Good agreement between the simulated and measured results is observed. The measured −10 dB impedance fractional bandwidth are 4.3% (2.38−2.484 GHz) and 60.6% (4.47−8.36 GHz) in the low‐ and high‐frequency bands, respectively, associated with peak gain values 0.64 and 6.22 dBi. The antenna's overall size is 0.22 λ L  × 0.20 λ L  × 0.006 λ L . The proposed antenna is a good candidate for multiple kinds of Wi‐Fi applications.